"Getting my Independence Back": Economic solvency program ideas from residents of a women's shelter. Issue 3 (27th February 2019) - Gilroy, Heidi; Nava, Angeles; Ellis, Pamela
Abstract: Objective: Intimate partner violence (IPV) is a serious public health issue that affects many women all over the world. One of the most consistent risk factors for IPV is poverty. On the other hand, IPV is also a risk factor for continued poverty, which puts many women in a cycle of violence and poverty that is difficult to escape. Interventions are needed to help women improve their economic solvency and decrease their poverty‐based risk for IPV. Design: The current study is a qualitative study to examine how women who have experienced IPV would plan and execute an intervention to improve economic solvency. Sample: The participants were 21 diverse women living in a women's shelter. Results: The major themes that came from the women's suggestions were as follows: addressing mental health, accountability, financial management classes, job skills and education, and other resources. Conclusion: Implications of this study include the need for more comprehensive programs, a general desire amongst the women for mentoring and accountability, and the need to address knowledge deficits about resources. This information can help resource providers to help build interventions to improve economic solvency in women who have experienced IPV and improve their overall safety.